Gamu-gamo sa Pugad Lawin - Santiago, Bobby ([Quezon City] Synergy)
This is a classic story of oppression and corruption, where father and son create a strong bond between themselves to stand up against the wrong-doings of rich gang-lord bent on the total destruction and oppression of small village.
VCD
Lito Lapid, Vic Vargas, Rio Locsin
Keywords: Corruption--Phils.; Action films; Feature films